The The Effect of Liquidity and Profitability on Financial Distress With Company Age as a Moderating Variable - Alin Nophiyanti; Nia Natia; Acep Komara (Universitas KH. Abdul Chalim Mojokerto, 2025)
The purpose of this study is to investigate the impact of liquidity and profitability ratios on financial distress, with firm age serving as a moderating variable. This study employs a quantitative approach with an associative methodology. The data used is secondary data from the financial statements of companies listed on the Indonesia Stock Exchange (IDX) for the years 2021-2023. The purposive sampling methodology was used for the sampling. This study analyzed 60 yearly financial reports. Multiple linear regression methods are used in this study's data analysis, as well as moderated regression. The findings indicated that liquidity had a favorable and significant effect on financial distress. Profitability has a favorable and considerable impact on financial stress. Profitability and liquidity have a substantial positive impact on financial distress. Company age reduces the impact of liquidity and profitability on financial hardship. The effect of liquidity and profitability on financial distress is 34.2%. Liquidity and profitability as well as the interaction of independent variables with moderating variables of company age, can predict financial distress by 35.1%.